2023
DOI: 10.3390/v15091893
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Type A Influenza Viruses Found in Swine Herds in Northwestern Poland from 2017 to 2019: The One Health Perspective

Lukasz Rabalski,
Maciej Kosinski,
Piotr Cybulski
et al.

Abstract: Influenza A viruses (IAV) are still a cause of concern for public health and veterinary services worldwide. With (−) RNA-segmented genome architecture, influenza viruses are prone to reassortment and can generate a great variety of strains, some capable of crossing interspecies barriers. Seasonal IAV strains continuously spread from humans to pigs, leading to multiple reassortation events with strains endemic to swine. Due to its high adaptability to humans, a reassortant strain based on “human-like” genes cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…The swine IAV from this study revealed a wide genotypic diversity in the study period, with most of the viruses belonging to 2009 pandemic lineage (H1N1pdm09). This is consistent with other reports in swine in the region and globally [ 7 , 19 , 29 ]. The genetic makeup of the pandemic H1 genes analysed in this study and their close relationship with pandemic and seasonal human IAV may suggest that these viruses continuously circulate within the swine population, possibly as a result of multiple reverse zoonotic events as reported in other studies [ 47–49 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The swine IAV from this study revealed a wide genotypic diversity in the study period, with most of the viruses belonging to 2009 pandemic lineage (H1N1pdm09). This is consistent with other reports in swine in the region and globally [ 7 , 19 , 29 ]. The genetic makeup of the pandemic H1 genes analysed in this study and their close relationship with pandemic and seasonal human IAV may suggest that these viruses continuously circulate within the swine population, possibly as a result of multiple reverse zoonotic events as reported in other studies [ 47–49 ].…”
Section: Discussionsupporting
confidence: 94%
“…Swine influenza viruses (SIV) are genetically diverse and classified into various genotypes based on their genetic makeup. These genotypes result from frequent reassortment events between swine, avian, and human influenza viruses [ 7 ]. The primary SIV genotypes include H1N1, H3N2, and H1N2, each with multiple lineages and sub-lineages reflecting their complex evolutionary history.…”
Section: Introductionmentioning
confidence: 99%